(untitled) - Gola, Mark (New York, 2007)
Contents: A complete baseball player; Hitting for average; Hitting for power; Defense; Arm strength; Speed...
Keywords: Baseball,Bóng chày; Scouting,Tìm hiểu; United States,Mỹ